Parameters of Governing Boards and the Goodwill of Listed Firms - Heraniah, Nicholas Ojiambo; Ondabu, Ibrahim Tirimba (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
Board characteristics are a key aspect of corporate governance practice and copious literature is available on the relationship between parameters of a governing board and the goodwill of listed firms. However, in spite of the abundant literature about this association and the progress in the day-to-day area of corporate governance, inconclusive results on the relationship still abound in previous studies. Thus, a study on the nexus between board characteristics and firm value is useful in understanding corporate governance practices especially in Kenya. This study is conducted with the main aim of establishing the effect of board characteristics (specifically the board meetings, board size and board gender diversity) on firm value of listed banks in Kenya. The study employed a correlational research design to attain its objective and with the target population of ten banks that were listed at the Nairobi Securities Exchange during the financial years between 2008 and 2021 using panel data. Multilinear regression is used for data analysis with the findings revealing that board gender had a positive but insignificant effect with firm value as proxied by Tobin’s Q, while board size had a positive and significant effect with firm value. On the other hand, board meetings had a negative and insignificant effect with firm value